Arbuscular mycorrhizal fungi community analysis revealed the significant impact of arsenic in antimony- and arsenic-contaminated soil in three Guizhou regions - Mi, Yidong; Xu, Chao; Li, Xinru; Zhou, Min; Cao, Ke; Dong, Cuimin; Li, Xuemei; Ji, Ningning; Wang, Fanfan; Su, Hailei; Liu, Xuesong; Wei, Yuan (Frontiers in Microbiology, 2023)
The lack of systematic investigations of arbuscular mycorrhizal fungi (AMF) community composition is an obstacle to AMF biotechnological applications in antimony (Sb)- and arsenic (As)-polluted soil. In this study, morphological and molecular identification were applied to study the AMF community composition in Sb- and As-contaminated areas, and the main influencing factors of AMF community composition in Sb- and As-contaminated areas were explored. The results showed that: (1) a total of 513,546 sequences were obtained, and the majority belonged to Glomeraceae (88.27%, 193 operational taxonomic units (OTUs)), followed by Diversisporaceae, Paraglomeraceae, Acaulosporaceae, Gigasporaceae, and Archaeosporaceae; (2) the affinity between AMF and plants was mainly related to plant species (F = 3.488, p = 0.022 < 0.050), which was not significantly correlated with the total Sb (TSb) and total As (TAs) in soil; (3) the AMF spore density was mainly related to the available nitrogen, available potassium, and total organic carbon; (4) The effect of soil nutrients on AMF community composition (total explanation: 15.36%) was greater than that of soil Sb and As content (total explanation: 5.80%); (5) the effect of TAs on AMF community composition (λ = –0.96) was more drastic than that of TSb (λ = −0.21), and the effect of As on AMF community composition was exacerbated by the interaction between As and phosphorus in the soil; and (6) Diversisporaceae was positively correlated with the TSb and TAs. Therefore, the potential impact of As on the effective application of mycorrhizal technology should be further considered when applied to the ecological restoration of Sb- and As-contaminated areas.